Dark Triad: Associations with juvenile delinquency, conduct disorder and trauma - Palma,Victor Hugo (2021)
Abstract The Dark Triad (DT) consists of three personality traits (machiavellianism, narcissism, and psychopathy). This is considered relevant for understanding the development of undesirable characteristics for society, frequently observed in young people and adults with antisocial and delinquent behaviours. Aversive personality traits have only recently aroused interest in researchers as a cohesive set of factors. The aim of this study was to analyse the associations of the DT (machiavellianism, narcissism, and psychopathy) with juvenile delinquency, conduct disorder (CD), and trauma. For this, a total sample of Portuguese adolescents (n=601; M age=15.95 years, SD=1.05 years, range=13-18 years) was used, subdivided into a male forensic group, male school group, and female school group. After the elaboration of multiple linear regression models, the results indicated that the psychopathy dimension was the one with the greatest association with juvenile delinquency and CD, while the narcissism dimension was the one with the greatest association with trauma. In future studies, the associations of the DT with juvenile delinquency, CD, and trauma in Portuguese adolescents should continue to be explored in the forensic and school contexts, to further clarify these relationships and contribute to the development and implementation of prevention and intervention programs for Youth with these characteristics.